Analisis Kinerja Personel Inspektur Angkutan Udara Otoritas Bandar Udara Wilayah III pada Optimalisasi Pengawasan Standart Pelayanan Minimal PT. Lion Mentari Airlines - Santi, Inayah Ari; Hilal, Raden Fatchul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In order to realize aviation safety, security and services, it is necessary to carry out control, supervision and investigation activities by air transport inspectors. Flight services provided by the Air Transport Business Entity for economy-class passenger services, Scheduled Commercial Air Transportation and domestic flight routes. The intended passenger service standards include several things, including pre-flight service standards, in-flight service standards, and post-flight service standards. Pre-flight service standards consist of: flight information, reservation, ticketing, check-in, boarding process, handling of flight delays, flight cancellations and enied boarding passes. Because the number of inspectors in carrying out supervision can also be an influential aspect of the results of the Minimum Standard Inspection of the service. This study aims to determine the factors that get the results of optimizing Air Transport Inspectors on Lion Air airlines. This research is descriptive using qualitative methods with data collection methods in the form of observation, interviews, and documentation. The data obtained is in the form of interviews with the Air Transport Inspector at the Surabaya Region III Airport Authority Office as well as documents used to carry out daily activities. The results of this study show the factors that constrain the control team of the Air Transport Inspector for Lion Air airlines on the Supervision Result Sheet instruments. Namely the unsupervised air transport inspector of airline officers directly at each airline service sub-unit due to a shortage of air transport inspector personnel. Keywords : supervision, performance, air transport inspector.